A privacy preserving and fine-grained access control scheme in DaaS based on efficient DSP re-encryption. (2018) - Yang, Jin; Wang, Liangming; Baek, Joonsang
Database as a service (DaaS) is an important cloud service, and preserving privacy is one of the most crucial needs in DaaS. To achieve more efficient and safer preservation of privacy in DaaS, a new access control scheme is proposed. Firstly, some definitions of data privacy value are introduced, which are used to formulate data tables. Then, an efficient DSP re-encryption mechanism is constructed based on the proposed data privacy value. Furthermore, the traditional DaaS service framework is improved to achieve more flexible and fine-grained access control. Finally, by combining the proposed mechanism with access control policy, our new access control scheme is carefully designed. Moreover, the correctness and security are analysed, which show that the new scheme is correct and IND-CCA secure under random oracle mode. That is, it can prevent conspiracy attacks effectively and protect the privacy of data owners and data users.